The Study of Water Quality in UTHM Residential College Pagoh by Filtration Process - POH QUAN, CHAN; ADINAZRIN, ADHAM SYAHIR; SAIFULLEZAN, AHMAD ASHRAFF HADANIE; ABDUL MALEK, KHAIRUL ZAMAN (Multidisciplinary Applied Research and Innovation, 2023)
This article explores the pipe water quality in UTHM Pagoh Residential College after filtration process. Generally, humans require clean water to consume in order to prevent the adverse health effects produced by pollutants in water. Therefore, water treatment is required to obtain clean water. One of the water treatment processes is filtration. The objectives of this study are to produce a water filter which consists of fine sand and crushed cockle shell with analysing the results of pH test, Biochemical Oxygen Demand (BOD) test, Total Suspended Solid (TSS) test and Ammoniacal Nitrogen (NH3-N) test on the filtered water. Fine sand and crushed cockle shell are used as the main composition for the drinking water filter. Three different filters has been used in this study. The composition of Filter A consists of 0.5 kg of fine sand only. Filter B consists of 0.5 kg of crushed cockle shell. Filter C consists of 0.25 kg of fine sand and 0.25 kg of crushed cockle shell. Quality of filtered water is better than ordinary pipe water.